The Effect of using Nearpod on Students’ Reading Comprehension and Students’ Participation in Studying English - Kalsum, Ifa; Sada, Clarry; Ikhsanudin, Ikhsanudin (Universitas PGRI Sumatera Barat, 2024)
This research investigated the effect of using Nearpod on Students’ Reading Comprehension and Students’ Participation during the English learning process. The objectives were to analyze the significance of Nearpod's impact on students' reading comprehension, assess the magnitude of this impact, and evaluate students' participation during the learning sessions. The methodology employed quasi-experimental design with non-equivalent control groups, involving both experimental and control groups. Data collection included pre-tests, post-tests, and questionnaires. The research targeted was Grade 9 students. The research utilized objective tests comprising 20 items and questionnaires as instruments. The findings indicated a positive effect of Nearpod on students' reading comprehension, albeit with a small effect size. Moreover, students demonstrated active participation during learning sessions using Nearpod. Therefore, the researcher recommends that teacher employ Nearpod as a tool to teach reading comprehension and to attract the students’ active participation in learning process.